PROBLEMS OF UNAUTHORIZED INTERFERENCE TO THE WORK OF UAV AND METHODS OF ITS SOLVING - Kozliuk, I. O.; Bakhtiiarov, D. І.; Lavrynenko, O. Y.; Tretiak, І. V. (Science-based technologies, 2016)
This article is sanctified to the actual subject -research of unmanned aerial vehicles(UAV). The flow diagram of UAV is shown in this scientific work, the information about advantages, prospects and methods of UAV application in the different spheres of life is brought up. The basic methods of unauthorized access to management and software are analysed. The examples of unauthorized interference to the work of UAV control system are shown and the possible solutions of UAV defence are offered. Anapparatus, which gives an opportunity to find out the place of UAV stay on certain territory and report about it, is analysed.The list of developing safe methods of counteraction to the UAV is given to consideration. The questions of home soldiery unmanned aerial vehicles, that become more important with every day, are considered. The types of possible attacks are analyzed. It is educed that basic defense is still the cryptosystem of UAV control system defense. This article allows you to delve into the issues and benefits caused by new unmanned aerial techniques, understand the seriousness of the problems and prospects, the ability to research and development in this direction.